Optimization and Validation of An Isocratic HPLC-UV Method for the Simultaneous Determination of Five Drugs Used in Combined Cardiovascular Therapy in Human Plasma - Soltani, Somaieh; Jouyban, Abolghasem (Asian Journal of Chemistry, 2010)
The validation of a simple isocratic HPLC-UV method for simultaneous quantification of 5 drugs (used in combination therapy protocols in cardiovascular disorders) in spiked human plasma was reported in this paper. A MZ-analytical column (15 mm × 4.6 mm, 5 μm) was used to separate carvedilol, losartan, diltiazem, furosemide and propranolol under an isocratic condition of acetonitrile/2-propanol/15 mM phosphate buffer (pH = 2) (32.5/2.5/65 v/v/v) mobile phase. The sample preparation consisted of a protein precipitation procedure using a mixture of acetonitrile and zinc sulphate solution prior to injection of sample to the chromatographic system. The maximum wavelength for the all detections was 225 nm. Method was validated according to the food and drug administration guidance for bio-analytical method validation. Method showed acceptable precision, accuracy and linearity [carvedilol (0.025-0.800 μg/mL), losartan (0.050- 0.800 μg/mL), diltiazem (0.050-0.800 μg/mL), furosemide (0.025-0.800 μg/mL) and propranolol (0.025-0.800 μg/mL)]. The method was robust and reproducible and the mean recoveries were in the range 99.0-104.4 %.